Propuesta de Creación de una Oficina para el Manejo de Proyectos (PMO) en la Compañía ABC - Navarro-Varela, Allan; Ramírez-Mota, Jennifer (Instituto Tecnológico de Costa Rica, 2012)
This research proposes the creation of a Project Management Office planned in the Sales, Distribution and Collections (SD&C) organization which is part of the IT area within the ABC Company, this organization focuses on the implementation of technical applications by creating innovative solutions to the above processes. The significant growth in the number of projects as well from members, who are part of the organization in Latin America, causes more complexity, making it essential a change to achieve effective coordination and standardization in the area of project management. The use of different methodologies, the various types of procurement and developers of these, and the limited experience and training in project management of human resources create problems of cost, delivery time, quality and added value, a situation that can get worse by the fast increase in the number of projects in the Sales, Distribution and Collections organization. For the development of the objectives of this study, data was collected through field research and through the application of a questionnaire that was used to analyze the situation of the organization SD&C. Likewise, it was conducted an investigation with applied character with a high descriptive component, which facilitated the identification of the level of maturity in project management within the organization, determining the continuity improvement model and features of the project Management Office in accordance with the particularities of the organization and according to their level of maturity in project management. This research identified that the organization SD&C is in the maturity level three, which according to the Heerkens model is the “Managed” level, that is why is important to propose a continuity improvement model to develop successful projects, moreover it was identified the type of PMO recommending the “Control Tower” as the most relevant. As well, it was define its ideal structure, roles, responsibilities and functions, and finally proposed performance indicators for monitoring and project management. Creating a project management office in SD&C allows continuity improvement in their processes, focus on best practices, development and training of human resources, encourage an organizational culture oriented towards projects, and measure their performance; all with the aim of achieving successfully targets in cost, time, scope and quality.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2012.
Keywords: Gestión de proyectos; Administración; Planificación; Mejoramiento continuo; Tecnología de la información